Three-dimensional strain at foreland arch transitions: structural modeling of the southern Beartooth arch transition zone, northwest Wyoming - Neely, Thomas Gardner, author; Erslev, Eric A., advisor; Charlie, Wayne A., committee member; Magloughlin, Jerry F., committee member (Colorado State University. Libraries, 2006)
Basement-involved foreland orogens commonly exhibit anastomosing networks of bifurcating basement arches whose structural culminations are linked by complex transition zones. Transitions between arches of differing orientation and vergence display structural complexity, commonly characterized by suites of diversely-oriented faults and folds. This study addresses the detailed geometry, the controls on along-strike changes in geometry, and the role of secondary structures at foreland arch transitions. Data from 1,581 slickensided minor faults, more than 1,000 km of 2D seismic data, and 187 wells were used to define a regional kinematic model, 16 balanced cross-sections, and restorable 3D surface models within the southern Beartooth arch transition zone. This transition zone is composed of three primary fault systems, the N-striking Beartooth Fault system, the NW-striking Line Creek Fault system, and the N-striking Oregon Basin Fault, as well as the Rattlesnake Mountain and Pat O’Hara Mountain hanging-wall backthrust structures. Slickensided minor faults from areas away from steeply-dipping fold limbs indicate a regionally-consistent 065° compression and shortening direction. Minor faults from the flanks of the Beartooth arch, Pat O'Hara Mountain, Rattlesnake Mountain, and Canyon Mouth anticlines show ideal σ1 and shortening directions oblique to both local fold trends and the regional 065° signature. This oblique-slip may have resulted from vertical-axis rotation, fold-related stress refraction, and/or strain partitioning between strike-slip and thrust faulting, perhaps during movement on pre-existing basement weaknesses. The Oregon Basin Fault and Beartooth Fault system show minimal folding of the basement surface, whereas the Line Creek Fault system shows basement surface folding near fault cut-offs up to approximately 25°. The Beartooth and Line Creek Fault systems are characterized by multiple fault splays and slip transfer between splays, and the Oregon Basin Fault is a single fault whose hanging wall is monoclinally-folded into the footwall of the Line Creek Fault system. Restorable, 2D basement block models of the Line Creek and Rattlesnake Mountain Fault systems suggest that the two are linked at depth and were active synchronously during progressive, rigid-block rotational backthrusting of the Line Creek Fault hanging wall. Three-dimensional restoration of the basement surface suggests that 1) shortening in the area is greatest on the Beartooth and Oregon Basin Fault systems and that comparatively less shortening occurred on the Line Creek Fault system, and 2) regional, clockwise vertical-axis rotation of several degrees may have occurred within the Beartooth and Line Creek Fault systems. Although both abrupt and gradual structural transitions are present within the area, the primary fault systems bounding the Beartooth arch and northwest margin of the Bighorn Basin are best characterized as defining gradual and continuous structural transitions. Secondary basement-involved structures in the area likely resulted from reactivation of pre-existing basement structures and do not appear to have accommodated large-scale rotations or changes in shortening direction.
Department Head: Sally J. Sutton.